Do Foreign-Owned Firms Have a Lower Innovation Intensity Than Domestic Firms? - Martin Falk; Rahel Falk (Austrian Institute of Economic Research (WIFO), 2006)
This paper addresses the question of whether foreign ownership matters regarding innovation intensity. It is well documented that foreign firms display lower innovation and R&D intensity than local firms do. However, (foreign) investors bear not only innovation performances in mind when making up their investment decisions. Unless factors such as firm size, labour productivity, skill and export intensity, sectoral affiliation and geographical area of operation are not properly controlled for, one is running the risk of comparing apples and oranges. To account for the selectivity bias we employ matching estimators when comparing the innovation intensity between domestic and foreign-owned firms. The observed gaps in innovation intensities do not only survive this matching test, but turn out higher as compared to the results that would have been derived from conventional regression analyses.
Keywords: 330; Foreign ownership; Multinational firms; propensity score matching; innovation expenditures; Multinationales Unternehmen; Eigentümerstruktur; Innovation; Industrieforschung; Schätzung; Österreich; Probit-Modell